Le gouvernement des suisses ou l'histoire en contrepoint essai - Chevallaz, Georges-André 1915-2002 (Ed. de l'Aire, 1989)
Analisi: POLITICA. Storia. Svizzera.
Keywords: Geschichte; Politik; Politisches System; Schweiz; Switzerland -- History; Switzerland -- Politics and government